Aiding the Transition to College: A Peer Mentoring Program for First-Year Student-Athletes - Morrissey, Timothy J.; Helfrich, Jennifer L. (My University, 1996)
The use and potential effectiveness of peer mentoring programs for student-athletes was explored. Issues for first-year student-athletes were presented as they justify aneed for additional support and guidance which older peers could effectively offer. This article described one university's effort to support and increase student development in intercollegiate athletics through a peer mentoring pilot program.The program's design, implementation, and future directions were discussed.
Keywords: sex/gender; race; career development; academic support; demographics